Dagboek 1970 - Wolkers, Jan 1925-2007 (Bezige Bij, 2012)
Dagboek van de Nederlandse schrijver (1925-2007) over het jaar 1970
Keywords: Wolkers, Jan / (Jan Hendrik) / 1925-2007; Wolkers, Jan -- 1925-2007; Tagebuch -- 1970